Landscape of toxin-neutralizing therapeutics for snakebite envenoming (2015–2022): setting the stage for an R&D agenda - Borri, Juliette (2024)
Snakebite envenoming (SBE) is a neglected tropical disease that exerts a high impact worldwide, especially in sub-Saharan Africa, Asia, and Latin America. Animal-derived antivenoms constitute the only specific, scientifically validated treatment for envenomings, although new therapeutic alternatives are being pursued. Despite the relevance of this disease, there is a critical lack of data on the research and development landscape in antivenoms and novel therapeutics. This study describes a thorough search of the state of SBE therapeutic market and research pipeline. A total of 127 marketed products and 196 candidates were identified. The current antivenom landscape is characterised by a homogeneous market of similar but geographically bespoke products needing improvement. The R&D pipeline analysis component revealed a diverse but immature picture since only eight candidates are in clinical development. This article interprets the findings of the study to provide an initial list of priority areas that sets the stage for further development of an R&D agenda to ensure translation of innovation to reduce the impact of SBE.